2005
DOI: 10.1016/j.rapm.2005.04.001
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Four Stimulation Patterns in Axillary Block

Abstract: Musculocutaneous-nerve stimulation and radial-nerve stimulation play predominant roles in the success of axillary brachial plexus block, although a triple-nerve stimulation technique is still required to produce complete anesthesia of the upper limb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…Multiple injections block the brachial plexus more successfully and rapidly than one injection when guided by surface anatomy, paraesthesia or electrical neurostimulation [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple injections block the brachial plexus more successfully and rapidly than one injection when guided by surface anatomy, paraesthesia or electrical neurostimulation [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…by a nerve stimulator and separately injected, reportedly provides a short onset time [24,25]. Zhao et al showed that a complete block could be obtained in 94.4% of patients receiving a low concentration of levobupivacaine (36 mL, 0.1%) using this technique [30].…”
mentioning
confidence: 99%
“…As the success rate in our study for radial nerve blockade was lower in the two-injection group, multiple-injection technique must be preferred in the surgical procedures to be performed on the areas innerved by the radial nerve. If the smaller number of injections is preferred, the radial nerve must be blocked separately (15 musculocutaneous nerve, median nerve and radial nerve in the other group. They found similar patient satisfaction rates in both the groups, and an additional drug requirement for sedation was less in the multiple injection group.…”
Section: Discussionmentioning
confidence: 99%